2021
DOI: 10.1007/s41775-021-00110-z
|View full text |Cite
|
Sign up to set email alerts
|

Remittances, financial development and the effectiveness of monetary policy transmission mechanism in Nigeria: a DSGE approach (1986–2018)

Abstract: The study examines the effect of remittance inflows on the effectiveness of monetary policy transmission channels in Nigeria using the New-Keynesian DSGE model. The study employs quarterly data spanning from 1986:1 to 2018:4. Four different channels are considered namely interest rate, exchange rate, credit and expectation channels. Results show that remittance inflows hinder the effectiveness of monetary policy channels. This implies the bulk of remittance inflows into the country do not pass through the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The DSGE results showed that unanticipated shock had short-run impacts on the transmission mechanism while anticipated had long-run impacts. Also, Apanisile and Osinubi (2020) examined the effectiveness of the monetary transmission mechanisms in the face of financial sector development in Nigeria between 2004:1 and 2016:4; by estimating the sticky-price DSGE model using a Bayesian approach. The results showed that the credit channel was the most active in stimulating output, while expectation channel was the most active channel in stabilising prices.…”
Section: Review Of Extant Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…The DSGE results showed that unanticipated shock had short-run impacts on the transmission mechanism while anticipated had long-run impacts. Also, Apanisile and Osinubi (2020) examined the effectiveness of the monetary transmission mechanisms in the face of financial sector development in Nigeria between 2004:1 and 2016:4; by estimating the sticky-price DSGE model using a Bayesian approach. The results showed that the credit channel was the most active in stimulating output, while expectation channel was the most active channel in stabilising prices.…”
Section: Review Of Extant Literaturementioning
confidence: 99%
“…Estimating the DSGE model could be a herculean task if the appropriate technique is not used. Several authors (Ajemian, 2013;Akinlo and Apanisile, 2019;Apanisile and Osinubi, 2020) have favoured Bayesian estimation techniques over all other available techniques. The preference for Bayesian approach arises because of the identification problem and lack of precision that may be encountered when other techniques are used.…”
Section: Empirical Analysismentioning
confidence: 99%
See 3 more Smart Citations